Crack healing in an alumina/silicon carbide nanocomposite after grinding and annealing - Wu, H; Titchmarsh, J; Roberts, S; Derby, B (Materials Research Society, 2000)
Alumina/silicon carbide nanocomposites are known to show their highest strength levels after surface grinding followed by annealing. After annealing in flowing argon, nanocomposites with very coarsely ground surfaces have strengths exceeding those with a finely polished surface. Specimens with lapped surfaces also show a small improvement in strength on annealing. TEM investigations of annealed cross-sections show that the annealing process leads to surface crack healing. The chemical composition of the subsurface region has been studied, and reactive products on and close to the nanocomposite surface after annealing have been investigated by energy dispersive X-ray analysis in the STEM.